2023
DOI: 10.3390/polym15030554
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of Biodegradable Poly(butylene adipate-co-terephthalate) Composites Reinforced with Novel AgSnO2 Microparticles for Application in Food Packaging

Abstract: Biodegradable composites with antimicrobial properties were prepared with microparticles of silver stannate (AgSnO2) and poly(butylene adipate-co-terephthalate) (PBAT) and tested for applications in food packaging. The PBAT matrix was synthesized and confirmed by 1H-nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction (XRD). Ultrasonic and coprecipitation methods were used to synthesize AgSnO2. A two-step mixing method and a solvent cast technique were utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…5,11 Biodegradable natural polymer films, e.g., starch films, offer alternatives to conventional packaging due to their excellent biodegradability, biocompatibility, renewability, and ease of processing with a wide range of potential applications. 12 Shende et al 11 reported that silver-doped titanium dioxide nanoparticles (NPs) encapsulated with the chitosan−poly-(vinyl alcohol) (PVA) film offer very high synergistic antimicrobial activity, which is similar to the study of Usman et al 13 for polymer PVA/GO/starch/Ag nanocomposite films. Silver nanoparticles are highly reactive due to a large surfaceto-volume ratio.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…5,11 Biodegradable natural polymer films, e.g., starch films, offer alternatives to conventional packaging due to their excellent biodegradability, biocompatibility, renewability, and ease of processing with a wide range of potential applications. 12 Shende et al 11 reported that silver-doped titanium dioxide nanoparticles (NPs) encapsulated with the chitosan−poly-(vinyl alcohol) (PVA) film offer very high synergistic antimicrobial activity, which is similar to the study of Usman et al 13 for polymer PVA/GO/starch/Ag nanocomposite films. Silver nanoparticles are highly reactive due to a large surfaceto-volume ratio.…”
Section: Introductionmentioning
confidence: 57%
“…Polymeric nanoparticles, such as alginate, nanocurcumin, and chitosan, also show antimicrobial activities . Nanoparticles can be used to make versatile materials for packaging and coating in the food industry. , Biodegradable natural polymer films, e.g., starch films, offer alternatives to conventional packaging due to their excellent biodegradability, biocompatibility, renewability, and ease of processing with a wide range of potential applications . Shende et al reported that silver-doped titanium dioxide nanoparticles (NPs) encapsulated with the chitosan–poly­(vinyl alcohol) (PVA) film offer very high synergistic antimicrobial activity, which is similar to the study of Usman et al for polymer PVA/GO/starch/Ag nanocomposite films.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of PBAT/kaolin composites via solution mixing and drop casting [ 36 ] is shown in Figure 1 . In 100 mL of chloroform, 2.0 g of PBAT polymer pellets were dissolved over a period of constant stirring to form a clear solution.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Biodegradable polymers can be either natural such as starch, cellulose, poly(butylene adipate-co-terephthalate), or synthetic like polylactide (PLA) polyhydroxyalkanoates, and polycaprolactone (PCL). [3][4][5][6] PCL is a common biocompatible, biodegradable, hydrophobic, and flexible linear aliphatic polyester. 7 The degradation of PCL in the human body proceeds by hydrolysis of the aliphatic ester bonds to produce natural and nontoxic metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biodegradable polymers have received much attention as potential alternatives to nonbiodegradable polymers and plastics as they can be easily degraded in the environment by microorganisms leading to less accumulation of polymer waste and consequently less pollution 1,2 . Biodegradable polymers can be either natural such as starch, cellulose, poly(butylene adipate‐co‐terephthalate), or synthetic like polylactide (PLA) polyhydroxyalkanoates, and polycaprolactone (PCL) 3–6 . PCL is a common biocompatible, biodegradable, hydrophobic, and flexible linear aliphatic polyester 7 .…”
Section: Introductionmentioning
confidence: 99%